The principles and practice of magnetic instrumentation for natural orifice transluminal endoscopic surgery and other limited access surgical operations - Cahill, R; Lewin, R; Mortensen, N; Jones, H (2010)
Natural orifice transluminal endoscopic surgery (NOTES) is viewed as a means of breaking one of the physical barriers associated with invasive abdominal operation by decoupling body wall injury from the surgical intervention. However, although the global concept has been clearly elucidated, there remains many separate components that still need piecing together before its routine practice can be realized. In particular, NOTES, in common with other confined access approaches such as single-port laparoscopic surgery, imposes marked constraints on the range and fluidity of operator instrument movement. Therefore, at present, these techniques possess significant limitations on their capacity for ensuring sufficient instrument triangulation as well as the appropriate degrees of tissue positioning and tensioning for facilitating efficient dissection. These technical considerations have recently reinvigorated the investigation of the utility of magnets in affecting surgical operation. The majority of work to date has however focused solely on permanent magnets due to their ease of manufacture and handling, despite the significant limitations inherent in their physical qualities. This review considers these issues and presents the potential engineering solution achievable by employing high-temperature superconducting electromagnets to impose the required physical forces for effective surgical operation in place of conventional rigid assistance instrumentation. © 2010 Authors.